Debt Relief Melalui HIPC Initiatives dan Tantangan Mengatasi Kemiskinan Dunia - Rochayati, Nurul; Maria, Suzanne, Departemen Ilmu Hubungan Internasional, FISIP UI (Global: Jurnal Politik Internasional, 2005)
Poor countries' debt crisis has caused severe impacts on humanity as it restrains development and poverty eradication efforts. This article will discuss the origins of debt crisis in poor countries, and the previous debt relief mechanisms to address low-income countries unsustainable debt conducted by Paris Club and the IMF. Despite these efforts, low-income countries debt remains unsustainable, therefore in 1996, IMF with the World Bank launched Heavily Indebted Poor Countries Initiatives in order to assist these countries to achieve a sustainable debt and therefore smooth the progress of poverty eradication. This article will also elaborate the initiatives' efficacy in the past years. Finally, this article will try to give some possible recommendations for the initiatives and debt relief efforts as a whole.